2012
DOI: 10.1002/adma.201202219
|View full text |Cite
|
Sign up to set email alerts
|

Can Doping Graphite Trigger Room Temperature Superconductivity? Evidence for Granular High‐Temperature Superconductivity in Water‐Treated Graphite Powder

Abstract: Granular superconductivity in powders of small graphite grains (several tens of micrometers) is demonstrated after treatment with pure water. The temperature, magnetic field and time dependence of the magnetic moment of the treated graphite powder provides evidence for the existence of superconducting vortices with some similarities to high-temperature granular superconducting oxides but even at temperatures above 300 K. Room temperature superconductivity in doped graphite or at its interfaces appears to be po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 30 publications
21
106
0
Order By: Relevance
“…flat band high temperature superconductivity, 25,26,28 various magnetic orders 29 etc. Under an applied magnetic field, a Lifshitz transition induced by trigonal warping in rhombohedral trilayer graphene has been reported.…”
mentioning
confidence: 99%
“…flat band high temperature superconductivity, 25,26,28 various magnetic orders 29 etc. Under an applied magnetic field, a Lifshitz transition induced by trigonal warping in rhombohedral trilayer graphene has been reported.…”
mentioning
confidence: 99%
“…Similar TH measurements of the n-heptane treated graphite powder with superconducting like field hysteresis (as in [7,8]) show a completely different behavior. The influence of temperature on the TH curves is not monotonous in the whole applied field, see the crossing of the curves at ∼ 0.3 T in Fig.…”
Section: Magnetization Measurements On Graphite Powdersmentioning
confidence: 58%
“…RWA/T from SGL Carbon GmbH (Werk Ringsdorff, Germany) with very low impurity concentration (e.g., Fe < 0.19 µg/g). Further characterization of this graphite powder and the influence of water on its magnetization was thoroughly reported in [7]. In this study we found that if we follow the same procedure to treat the graphite powder with nheptane as was done with water, i.e.…”
Section: Magnetization Measurements On Graphite Powdersmentioning
confidence: 69%
See 2 more Smart Citations